EFEKTIVITAS STORY ACTING DALAM MENGAJARKAN MAGIC WORDS PADA ANAK USIA 5-6 TAHUN [THE EFFECTIVENESS OF STORY ACTING IN TEACHING THE MAGIC WORDS TO CHILDREN AGED 5-6 YEARS] - Krista, Philio Angeline; Septiana, Eva (Polyglot, 2026)
Children aged 5-6 were found to show impolite behavior, such as using harsh words because they are confused and yet accustomed to speaking politely. Difficulties in teaching polite expressions arose due to children’s limited focus, low interest, and tendency to forget the material. This study examined the effectiveness of story acting in teaching magic words to children aged 5-6. The aim was to improve children’s knowledge of magic words so they could communicate more polite with others. This study used one group pre-test post-test design, involving 11 children. The results showed significant improvements in the use of the words “sorry” (p=.008), “thank you” (p=.034), and “excuse me” (p=.018). However, no significant improvement occurred for “please” (p=.079). Furthermore, overall knowledge of magic words was not retained after a seven-days delay. These results indicate that story acting effectively enhances children’s understanding of “sorry”, “thank you”, and “excuse” though consistent reinforcement is essential to support understanding. Abstrak Bahasa Indonesia Ditemukan bahwa anak usia 5-6 tahun belum menunjukkan sikap sopan santun seperti berkata kasar karena anak bingung dan belum terbiasa mengucapkan bahasa sopan. Kesulitan dalam mengajarkan anak yaitu, anak tidak fokus, tidak tertarik, dan mudah lupa. Penelitian ini mengkaji efektivitas story acting dalam mengajarkan magic words untuk anak usia 5-6 tahun. Penelitian bertujuan meningkatkan pengetahuan anak mengenai magic words sehingga anak dapat bertutur kata sopan dengan orang lain. Penelitian ini menggunakan desain one group pre-test post-test. Sampel terdiri dari 11 anak usia 5-6 tahun. Hasil uji menunjukkan adanya peningkatan signifikansi pada kata “maaf” (p=.008), “terima kasih” (p=.034), dan “permisi” (p=.018) setelah intervensi. Sedangkan tidak adanya signifikansi pada kata “tolong” (p=.079) setelah intervensi. Namun, magic words menunjukkan data yang tidak signifikan setelah pemberian jeda tujuh hari dari intervensi. Temuan ini menekankan bahwa story acting meningkatkan pengetahuan anak mengenai kata “maaf”, “terima kasih”, dan “permisi”, serta membutuhkan dorongan pembelajaran untuk memahami materi magic words.